User Interface and User Experience Disaster Education Game Application Using Heuristic Evaluation: Usability User Interface Dan User Experience Aplikasi Game Edukasi Bencana Alam Menggunakan Metode Evaluasi Heuristic - Muhammad Subhana (bit-Tech, 2023)
Natural disaster educational game application to introduce Raudhatul Athfal (RA) level students to learning and knowledge. A game application was created to make it easier to recognize and complete a stage in the form of a game operated via computer, making it additional learning how to use a computer and knowing how to responsive and alert when a disaster strikes, what should be done through this application game? In order to better measure students' abilities when using this application, it is necessary to assess several respondents, one of whom is the teachers at the school, to assess whether this application will be of interest or not in understanding how to use it and other components. The assessment process is through distributing questionnaires and filling in the results through respondents using a Likert scale with heuristic evaluation indicators filled in with the statement that this application is interesting at the class size level for RA (Raudatul Athfal) students with a Visibility of system status score of 74, Match between system and real world tea 71, User control and freedom 58, Consistency and standards 72, Error prevention 64, Recognition rather than recall 73, Flexibility and efficiency of use 78, Helps users recognize diagnose 66, Recovers user 75, Help and documentation 79 with a total score of 710 using the Likert scale formula.